ECONOMIC EFFICIENCY OF CONTAINER TRANSPORTATION BY RAILWAY TRANSPORT - Savenko, O. S.; Muzyka, H. I.; Bekh, P. V. (Science and Transport Progress, 2005)
The article presents a method of calculating the costs of rail freight container services.